The Temperament and Character Inventory in women with migraine - Mongini, F. (Springer-Verlag, 2005)
The purpose of this work was to investigate: (1) the differences in temperament and character between 49 women with migraine and 49 controls using the Temperament and Character Inventory (TCI), and (2) the extent to which these differences were related to migraine or to the presence of comorbid depression. The migraine patients scored significantly higher than the controls in two temperament dimensions—Harm Avoidance (HA) and Persistence (P)—and significantly lower in one character dimension—Self-Directedness (SDir) (Student’s t). After multiple logistic regression, the TCI P and HA dimensions were significantly associated with the presence of migraine. The HA dimension was also related to the presence of depression. Our results show that in migraine the higher HA score could be partly associated to comorbid depression while the high P dimension seems to be solely related to the presence of migraine.